Modeling and Nonlinear Control of a Two-Wheeled Self Balancing Human Transporter - Jain, Saransh; Makkar, Mohit; Jain, Sarthak; Unune, Deepak (Journal of Applied Nonlinear Dynamics, 2026)
The two-wheeled self-balancing human transporters (TW-SBHT) are being widely used in transportation nowadays owing to their advantages such as energy saving, environmental protection, simple structure, and flexible operation. The modelling and control of TW-SBHT have emerged as one of the trending research areas in the field of control system design of mobile robots. Being a complex and nonlinear system, the control problem of TW-SBHT is a challenging task and needs to be effectively tackled to achieve the control objectives of maintaining uniform speed and dynamic stability. Though linear control strategies for TW-SBHT have been already proposed in the literature, they cannot offer an effective control for large external disturbances. Therefore, in this work, a non-linear control i.e. State-Dependent Riccati Equation (SDRE) has been implemented for effective control of TW-SBHT and its performance is compared with the linear controls including Proportional-Integral-Derivative (PID) and Linear-Quadratic Regulator (LQR) techniques. Initially, the more accurate model of TW-SBHT has been derived by applying the suitable modifications in existing models. Then, the application of SDRE for control of TW-SBHT has been presented and its performance is compared with linear control strategies.